Bureaucratic pathology a short analysis - Mohamed, Ahmad Martadha (Penerbit Universiti Utara Malaysia, 2005)
Max Weber (1946), in his classical analysis of bureaucracy points out that bureaucracy involves a clear-cut division of integrated activities. These activities are controlled through the assignment of roles that are based on technical qualifications. The technical experts are governed by general and abstract rules that necessitate the specific instructions for each specific case. This is done through the use of categorization whereby individual cases are classified into specific criteria and solved accordingly. Weber in his original definition of bureaucracy also outlines the importance of office hierarchy in which there is a supervision of the lower offices by the higher ones. When bureaucracy goes through various development processes, the principle of hierarchy has been "monocratically organized" (Weber: 5). This means that work is organized based on categorization.